Unmanned aerial vehicles trajectory analysis considering missing data - Wang, Bo; Kharchenko, Volodymyr; Kukush, Alexander; Kuzmenko, Nataliia (Transport, 2019)
Researches very often deal with the problem of missing data. This issue is caused by impossibility of data obtaining, its distortion or concealment. The goal of present paper is to recover missing data and to analyse Unmanned Aerial Vehicles (UAV) trajectory based on the degree of deviation from pre-planned trajectory. The range probability approach is used to assess flight situation. The results of trajectory analysis for real position data of UAV are demonstrated.